Morphometry and Cardiac Anatomicalsurgical Segmentation in Goats - Silva, Amanda Rafaela Nascimento da; Diniz, João Augusto Rodrigues Alves; Rocha, Ediane Freitas; Neto, Raphael Bernardo da Silva; Santos, José Rômulo Soares dos; Menezes, Danilo José Ayres de (Acta Scientiae Veterinariae, 2016)
Background: Although surgeries that remove of part of the heart wall are not yet part of veterinary and human surgical routine, experimental studies can indicate this practice in cases where alterations are identified in the heart morphology, with the determination of the heart segments that are part of the organ with independent vascularization and irrigation. In this context, the objective of the present study was to describe the anatomic surgical segmentation of the goat heart and supply biometric data on the heart to enrich data on the heart morphology of this species. Materials, Methods &Results: Twenty-six hearts were used from crossbred goats, ten to assess the topographical relations of the heart and morphological description of the organ; ten hearts were weighed on 0.01 g precision semi-analytical scales, measured with a pachymeter and later Agar-Agar was injected in the cavities which were sectioned crosswise to establish the volumetric proportion of the heart components, applying a point counting grid to the base surfaces; in three hearts natural latex was injected in the coronary arteries, that were later dissected, and red-stained vinyl acetate was injected in three, corroded in acid to make vascular molds and these two groups were used to define the irrigation territories of the coronary arteries, identifying the anatomic surgical units among the animals studied. The goat heart presented average weight of 126.6 g, 8.36 ± 0.62 cm length and 5.89 ± 0.57 cm width at the base. The study of the volumetric proportion showed that the proportion of muscle was 75.87% and the cavity proportion was 24.12%; the arterial volume (13.94% ±3.01) was greater than the ventricular volume (6.32% ± 1.43). An average of 13 ventricular segments were identified from the vascular study, coming from the right and left coronary arteries that were characterized as SAIP - Interventricular Paraconal Arterial Segment; SAVE1- Left Ventricular Ventral Arterial Segment; SAVE2- Left Ventricular Ventral Arterial Segment; SAME- Left Ventricular Margin Arterial Segment; SAVD1- Right Ventricular Ventral Arterial Segment, SAVD2 - Right Ventricular Ventral Arterial Segment, SAIS- Subsinuosus Interventricular Arterial Segment, SAA- Adipose Artery Arterial Segment, SADE1- Left Ventricular Dorsal Arterial Segment, SADE2- Left Ventricular Dorsal Arterial Segment 2- SAMD: Right Ventricular Margin Arterial Segment, SADD1- Right Ventricular Dorsal Arterial Segment, SADD2- Right Ventricular Dorsal Arterial Segment. Discussion: The goat hearts presented anatomy and topography according to that described in the literature for the species. Regarding the heart morphology and segmentation, the goat is similar to the dog, and the goat can be used as an experimental model in cardiology research. As the segments identified presented few variations among the animals, observing that some of them were not found in 100% of the sample, but understanding that the goat arterial segments are well defined in the heart wall, the data was considered reliable for future research of partial ventriculectomies.